Study Application of Student Center Learning Method in Fiqh Munakahat Learning - Muis, Abdul; Sibawaihi, Sibawaihi; Ali, Muhammad (Universitas Islam Negeri (UIN) Jurai Siwo Lampung, 2022)
The sophistication of technology that is now developing and the interaction of teenagers who can't be controlled today with the sophistication of technology certainly make parents' hearts become restless because, on the other hand, they have to learn online. Learning awareness which sometimes needs to be improved with online learning models makes lecturers have to look for the right method to be applied in online learning. Student Center Learning is one of the methods that can be applied in the online learning process because the SCL method makes students active in learning. The research method in writing this article uses a qualitative method with primary data in the form of a questionnaire which has obtained respondents from 78 students in the Munakahat Fiqh course with the achievement of students' understanding of the Munakahat Fiqh course getting a very effective score (A) ranging from 85-100 as many as 11 students, effective (B) ranged from 70 to 84 as many as 57 students, and less effective (C) ranged from 55 to 69 as many as 10 students.